PKM. PENYUSUNAN KURIKULUM OPRASIONAL SEKOLAH DI PENGGERAK ANGKATAN 2 PROVINSI BALI - I Wayan Sumandya; I Komang Sukendra; Made Irma Suryani; Dwi Prinicila Pramesuari (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
The last point of the Tri Dharma of Higher Education is community service. Community service is important to do through the service of curriculum preparation at the Driving School. The Motivating School Program consists of five interrelated and inseparable interventions. Assistance is carried out in order to produce school operational curricula according to the characteristics of each school. The learning committee who attended this service activity were 30 people from 5 schools, namely SMA N 1 Denpasar, SMAN 7 Denpasar, SMAN 4 Singaraja, SMAN 1 Seririt and SMAN 2 Gerokgak. There are activities carried out at the socialization stage, including: 1) Reflection on New Paradigm Learning, 2) Independent Learning on the Merdeka Teaching Platform, 3) Preparation of School Operational Curriculum, 4) Understanding Learning Outcomes, 5) Designing Learning, 6) Student Profile Strengthening Projects Pancasila, 7) Data-Based Planning, 8) Introduction of Priority Technology Platforms. The results obtained in this activity are that participants are able to: 1) Understand the New Paradigm Learning, 2) Use the Independent Teaching Platform, 3) Develop School Operational Curriculum, 4) Understand Learning Outcomes, 5) Design Learning, 6) Projects for Strengthening the Pancasila Student Profile, 7) Understanding Data-Based Planning, 8) Using Priority Technology Platforms. This activity will continue until mentoring for 2 years.